(untitled) (Environment & Health, 2015)
Objective. We studied the general and primary disability among children in the industrial cities with a high technological load and rural area with a less significant technological load, as well as in the Luhansk region in general during 1996-2013. Materials and methods. The estimation of primary and general disability in children under 17 years was performed on the basis of statistical data analysis of the annual reference books prepared by the Luhansk Regional Children’s Hospital. Results and summary. Among the causes of general and primary children`s disability in the region, industrial towns and rural areas, the congenital anomalies (Q00-Q99) come the first, diseases of the nervous system (G00-G99) come the second, mental and behavioral disorders (F00-F59) are the third. Among the causes of common disability, the disorders of eye and adnexa (H00 H59) come the fourth, the endocrine, nutritional and metabolic diseases (E00-E90) are the fifth. In the industrial cities with the large enterprises of black metallurgy and coke-chemical production, especially in Alchevsk, the endocrine, nutritional and metabolic diseases (as one of the main causes of general and primary children`s disability) are largely determined by the adverse environmental conditions and other factors of urban environment. Children`s disability in Alchevsk due to blood and hemopoietic organs’ diseases, cerebral palsy, eye and adnexa diseases, diseases of digestive system, diseases of the musculoskeletal system and connective tissue is also caused by the influence of technogenic environment. We noted a statistically significant regularity of the increase of disability for C00-D48, E00-E90, H00-H59, L00-L99, M00-M99, N00-N99 and Q00-Q99 classes of diseases, especially C00-D48, E00-E90 and Q00-Q99 classes. The preventive measures were developed.